Good governance practices: a preliminary analysis of Malaysian Government initiatives and its challenges, 2010-2017. - Jamaiudin, Norhaslinda (2018)
The notion of good governance has amiably been accepted and become a pillar in recent government reforms. As many believes the attainment of good governance would largely influences political stability and effectiveness within government administration. Introduced by United Nation agencies, this concept promotes fair, transparent, accountable, participative and inclusive type of governance. In the case of Malaysia, the overall orientation of good governance serves as the core part of public sector management and policy reforms. Under the influence of New Public Management approaches (NPM), these reforms, indeed have been consolidated with the embodiment of good governance framework. This can be seen through the implementation of National Transformation Policy (2010-2020). Since inception, the NTP has brought unprecedented changes in government decision making, institutional structures and policy outcomes. Guided by good governance model, this paper aims to examine Malaysia’s Outline Perspective Plan (OPP) under the National Transformation Policy which was introduced by former Prime Minister, Datuk Seri Najib Tun Abd Razak. This highly praised policy plan is predominantly viewed as inclusive, thus in line with good governance practices. However the key question to be posed at the outset is whether the implementation of the NTP and the achievement of intended policy outcomes as shown by statistical data would be felt by Malaysian citizens? Literally, does NTP embrace and uphold good governance principles? And what are the challenges encountered by the previous government? A preliminary analysis therefore is conducted to assess the implementation of NTP in the context of good governance practices. Descriptive analysis is used to determine the visibility of good governance features in NTP. In addition, quantitative data analysis is employed to measure public perception on the implementation of NTP as to confirm the presence of good governance practices in the implementation of NTP.